2013
DOI: 10.1017/s0033291713000731
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical effects of short-term antidepressant treatment in fMRI emotional processing models in volunteers with high neuroticism

Abstract: These results suggest that 7 days of SSRI administration can increase neural markers of fear reactivity in subjects at the high end of the N dimension and may be related to early increases in anxiety and agitation seen early in treatment. Such processes may be involved in the later therapeutic effects through decreased avoidance and increased learning about social 'threat' cues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
53
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 63 publications
6
53
1
Order By: Relevance
“…Another study found that 7 days of citalopram increased amygdala response to fearful faces, as well as to happy and neutral faces, in high-Ns [38]. This increased amygdala response to fearful faces is in contrast to both unselected healthy populations [23] and depressed patients [37].…”
Section: (C) Studies With High Neurotic Volunteersmentioning
confidence: 96%
See 1 more Smart Citation
“…Another study found that 7 days of citalopram increased amygdala response to fearful faces, as well as to happy and neutral faces, in high-Ns [38]. This increased amygdala response to fearful faces is in contrast to both unselected healthy populations [23] and depressed patients [37].…”
Section: (C) Studies With High Neurotic Volunteersmentioning
confidence: 96%
“…The effect of acute antidepressant treatment on neural activity in depressed participants remains to be explored. In particular, it would be interesting to see whether the neural correlates of the acute anxiogenic effects of SSRIs might be seen more clearly in this population than in healthy volunteers, as has been suggested [38].…”
Section: (B) Depressed Patient Studiesmentioning
confidence: 97%
“…These tasks required participants to indicate the type of emotion expressed in faces briefly presented on a computer screen (Attenburrow et al, 2003;Harmer, Rogers, et al, 2003;Kerestes et al, 2009). Adaptations were used by others (Beacher et al, 2011;Bilderbeck et al, 2013;Di Simplicio et al, 2013;Passamonti et al, 2012;Simonsen et al, 2014). For example, Beacher et al (2011) asked participants to rate faces in terms of attractiveness.…”
Section: Computer Tasks Used To Date Have Limited Ecological Validitymentioning
confidence: 99%
“…
In the Introduction to this paper (Di Simplicio et al 2013) the authors incorrectly refer to Bigos et al (2008) among a number of previous studies consistently showing a decreased amygdala response to negative versus positive facial expressions after single-dose antidepressant administration in unselected healthy volunteers. Contrary to the other findings cited, Bigos et al (2008) found an increased amygdala response to facial expressions after acute citalopram administration.

Instead, Bigos et al (2008) should have been cited in the Limitations paragraph, a corrected version of which is displayed below.

Limitations

The results from this study are limited by the absence of a low-N control group also receiving SSRI treatment to verify that the effects seen here are specific to a highly neurotic sample.

…”
mentioning
confidence: 99%
“…In the Introduction to this paper (Di Simplicio et al 2013) the authors incorrectly refer to Bigos et al (2008) among a number of previous studies consistently showing a decreased amygdala response to negative versus positive facial expressions after single-dose antidepressant administration in unselected healthy volunteers. Contrary to the other findings cited, Bigos et al (2008) found an increased amygdala response to facial expressions after acute citalopram administration.…”
mentioning
confidence: 99%